Application of molybdenum and a desiccant herbicide to the common bean under direct seeding (Revista Ciência Agronômica, 2015)
Applying micronutrients together with the herbicides used in plant desiccation can ensure an adequatesupply of these nutrients and a reduction in production costs under a direct seeding (DSS) system. The aim of thisstudy was to evaluate the effect of dosages of molybdenum (Mo), applied both in a desiccation operation together withglyphosate on the straw of brachiaria (Brachiaria brizantha) and separately via the leaves, on the common bean (cultivarOuro Vermelho) grown under DSS. A randomised block design was used with four replications in an arrangement ofsublots. In the lots, dosages of Mo (0, 0.1, 0.2, 0.4 and 0.8 kg ha-1) were applied together with the desiccant herbicide(glyphosate), and in the sublots, two dosages of Mo (0 and 100 g ha-1) were applied via the leaves. Two experimentswere carried out in the town of Coimbra, in the state of Minas Gerais, Brazil, one in 2009 and the other in 2010 (thesame treatments having been applied in the experimental area in 2008). Foliar fertilization was carried out with sodiummolybdate [(Na2MoO4) (39% Mo)] at stage V4 in the bean plants. The application of Mo, whether mixed with thedesiccant or applied via the leaves, had no significant effect on yield components or on productivity. Levels of Mo and N in thegrain, and of N in the leaves, increased with the application of Mo, both when mixed with the desiccant and applied via the leaves.